(untitled) (Marketing Journal, 2025)
The article analyzes the impact of environmental and innovative factors on the production efficiency of chemical industry enterprises. The necessity of taking into account the consolidated influence of environmental factors in the process of innovation imp lementation is scientifically substantiated. The role of the chemical industry in the economy and its importance in the export of chemical products are revealed. Existing approaches to assessing the effectiveness of innovations from the perspective of thei r environmental impact are examined. In addition, a conceptual № 1 357 approach is proposed that is aimed at a systematic assessment of the influence of environmental and innovative factors at all stages of the innovation process.